(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Medicinal plants are an important reservoir of bioactive compounds that may offer safer and effective alternatives for managing free-radical damage. Pereiria medica Lindl. (Tree turmeric), widely used in the indigenous system of medicine was studied for its in vitro scavenging activity. Objective: To evaluate the in vitro free-radical scavenging activity of the methanol stem extract of P. medica using DPPH and ABTS assays. Methods: Stem material was extracted with methanol and tested at multiple concentrations for radical-scavenging activity by DPPH and ABTS spectrophotometric assays. Data were analyzed by linear regression to determine concentration–response relationships and IC50 values. Results: The methanol stem extract exhibited concentration-dependent radical scavenging in both assays. Calculated IC50 values were 57.10 μg/mL (DPPH) and 53.63 μg/mL (ABTS), indicating comparable potency across the two radical systems. Conclusion: The methanolic stem extract of P. medica demonstrated significant in vitro antioxidant activity, supporting its traditional use and warranting further phytochemical characterization and in vivo evaluation.